Isolation and characterization of keratinolytic bacteria from chicken farm bed and its application on production of keratin hydrolysates from chicken feather - Prajapati, Saugat; Anal, Anil Kumar; Loc Thai Nguyen; Datta, Avishek; Sadiq, Muhammad Bilal; Wonnop Visessanguan; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
The aim of this research was to isolate a potential keratinolytic bacterial strain from chicken farm bed and use it to produce keratin hydrolysates from chicken feather. In addition, the physicochemical and bioactive properties of the produced keratin hydrolysates was studied. Isolation was carried out by spread plate method in skim milk agar (SMA) plates followed by growing in whole feather broth to study their keratin hydrolyzing activities. As a result, a bacterial strain KB1 was isolated with immense keratin hydrolysis. The BLAST search result of 16s rDNA sequence against the database showed that strain KB1 is 99.78% similar with Bacillus siamensis and Bacillus velezensis. The fermentation process was optimized by using Response surface methodology and Box-Behnken design. The optimum fermentation condition (desirability: 0.976) was found at 40oC, initial pH of 8.84 and 1% (w/v) feather concentration with the production of 252.95 mg/g of soluble protein and 88.19% feather degradation respectively. For feather. The keratin hydrolysate contained 78.45 % protein with 82.36 % digestibility. The IC50value of keratin hydrolysate for DPPH free radical scavenging activity was found to be 0.7 mg/ml and ferric reducing value of 130.41og AAE/ml.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 2018
Keywords: Keratin; Bacteria; Bioactive compounds -- Biotechnology